D-galactose induces astrocytic aging and contributes to astrocytoma progression and chemoresistance via cellular senescence - Hou, Jingang (Mol Med Rep, 2019)
The administration of D-galactose triggers brain aging by poorly understood mechanisms. It is generally recognized that D-galactose induces oxidative stress or affects protein modifications via receptors for advanced glycated end products in a variety of species. In the present study, we aimed to investigate the involvement of astrocytes in D-galactose-induced brain aging in vitro. We found that D-galactose treatment significantly suppressed cell viability and induced cellular senescence. In addition, as of the accumulation of senescent cells, we proposed that the senescence-associated secretory phenotype (SASP) can stimulate age-related pathologies and chemoresistance in brain. Consistently, senescent astrocytic CRT cells induced by D-galactose exhibited increases in the levels of IL-6 and IL-8 via NF-κB activation, which are major SASP components and inflammatory cytokines. Conditioned medium prepared from senescent astrocytic CRT cells significantly promoted the viability of brain tumor cells (U373-MG and N2a). Importantly, conditioned medium greatly suppressed the cytotoxicity of U373-MG cells induced by temozolomide, and reduced the protein expression levels of neuron marker neuron-specific class III β-tubulin, but markedly increased the levels of c-Myc in N2a cells. Thus, our findings demonstrated that D-galactose treatment might mimic brain aging, and that D-galactose could contribute to brain inflammation and tumor progression through inducing the accumulation of senescent-secretory astrocytes.